2016
DOI: 10.2147/ndt.s79354
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to improve anxiety and depression in patients with COPD: a mental health perspective

Abstract: Chronic obstructive pulmonary disease (COPD) is a chronic inflammatory lung disease characterized by progressive and only partially reversible symptoms. Worldwide, the incidence of COPD presents a disturbing continuous increase. Anxiety and depression are remarkably common in COPD patients, but the evidence about optimal approaches for managing psychological comorbidities in COPD remains unclear and largely speculative. Pharmacological treatment based on selective serotonin reuptake inhibitors has almost repla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
87
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(100 citation statements)
references
References 268 publications
(223 reference statements)
1
87
0
5
Order By: Relevance
“…Currently, the findings of randomised controlled trials pointed out that activity with breathing with 15 min per time, twice a day for 12 weeks improved depression (Cheng, Wang, Chou, & Yeh, 2018) and heart failure patients' anxiety (Teng, Yeh, & Wang, 2018). However, the effects of anxiety and depression are limited for patients with COPD (Tselebis et al, 2016).…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the findings of randomised controlled trials pointed out that activity with breathing with 15 min per time, twice a day for 12 weeks improved depression (Cheng, Wang, Chou, & Yeh, 2018) and heart failure patients' anxiety (Teng, Yeh, & Wang, 2018). However, the effects of anxiety and depression are limited for patients with COPD (Tselebis et al, 2016).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Chronic obstructive pulmonary disease (COPD) is a treatable but high burden disease that has negative impacts on patients’ bio‐psychological well‐being such as anxiety, depression (Tselebis et al, ), dyspnoea (Chang, Dai, Chien, & Chan, ; Yeh, Chen, Liao, & Liao, ) and quality of life (Blakemore et al, ). Relieving these symptoms and improving quality of life are targeted to manage COPD patients.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, one of the primary reasons for individuals with pulmonary disease to undergo pulmonary rehabilitation is alleviation of anxiety. One study reported rates of depression at 37%‐71%, and rates of anxiety at 50%‐75% in patients with severe COPD disease [82]. Anxiety in patients with CLD is intimately linked with patients' fears of acute dyspnea attacks with a sense of suffocation and fear of death [82].…”
Section: Special Considerations In Lt Recipients In the Acute Rehabilmentioning
confidence: 99%
“…One study reported rates of depression at 37%-71%, and rates of anxiety at 50%-75% in patients with severe COPD disease [82]. Anxiety in patients with CLD is intimately linked with patients' fears of acute dyspnea attacks with a sense of suffocation and fear of death [82]. These comorbid psychological impairments have been implicated to predict increased functional impairment, disability, morbidity, lower QOL, and decreased adherence to treatment [82].…”
Section: Special Considerations In Lt Recipients In the Acute Rehabilmentioning
confidence: 99%
“…In a recent meta-analysis, researchers showed that adding psychotherapy to antidepressant medications was twice as effective as compared to antidepressant treatment alone 16 in reducing depressive symptoms. However, evidence regarding combination therapy use in the management of depression in COPD population has been limited 17 .…”
Section: Introductionmentioning
confidence: 99%